2016
DOI: 10.1590/s1984-82502016000300006
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility patterns among bacteria isolated from intensive care units of the largest teaching hospital at the northwest of Iran

Abstract: This study was conducted to determine the antimicrobial susceptibility patterns among common pathogens in the intensive care units (ICUs) of a university hospital in northwestern Iran. A retrospective study was done on laboratory records of patients with nosocomial infection who were admitted to five ICUs of Imam Reza Hospital during a 21-month period from March 2010 to January, 2012. A total number of 556 isolates from 328 patients were evaluated. The most common sites of infections included respiratory (51.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
4
11
0
1
Order By: Relevance
“…Consistent with our study, other investigators have reported also as the most common site of infection respiratory tract, urine and blood [3,7,12].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our study, other investigators have reported also as the most common site of infection respiratory tract, urine and blood [3,7,12].…”
Section: Resultssupporting
confidence: 93%
“…Almost 55% from the Acinetobacter strains were MDR (resistant to cephalosporins, carbapenems and fluoroquinolones). High rates of MDR were found for Pseudomonas (73.07%), MRSA (62.03%) and Klebsiella (44.57%), much higher than those found in other studies [12]. Less than one-third of E. coli strains were multidrug-resistant.…”
Section: Resultsmentioning
confidence: 60%
“…Consistent with our study, other investigators have reported also as the most common site of infection respiratory tract, urine and blood [3,19,[25][26][27].…”
Section: Resultssupporting
confidence: 93%
“…In addition, many of the drugs employed can give rise to inhibition of their immune response [14]. The different studies have reported that the most commonly isolated organisms in patients in ICU comprise gram-negative bacilli (GNB), mainly Enterobacteriaceae species, and non-fermenting gram-negative bacilli (NF-GNB), such as Pseudomonas and Acinetobacter species [13,15,16]. GNB were responsible for 45–70% of ventilator-associated pneumonias, for 20–30% of vascular pathway infections (catheter), and for commonly caused infections in surgical wounds and in the urinary tract that led to sepsis [17].…”
Section: Introductionmentioning
confidence: 99%